2005
DOI: 10.1038/sj.cdd.4401764
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of UV-induced apoptosis by the human DNA repair protein XPG

Abstract: The severe xeroderma pigmentosum/Cockayne syndrome (XP/CS) syndrome is caused by mutations in the XPB, XPD and XPG genes that encode the helicase subunits of TFIIH and the 3 0 endonuclease of nucleotide excision repair (NER). Because XPB and XPD have been implicated in p53-mediated apoptosis, we examined the possible involvement of XPG in this process. After ultraviolet light (UV) irradiation, primary fibroblasts of XP complementation group G (XP-G) individuals with CS enter apoptosis more readily than other N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…Instead, cells escape replicative arrest utilizing DNA damage tolerance mechanisms that include error-free and error-prone DNA repair systems (36). We and others have shown that UV radiation-induced apoptosis is decreased in XPC -/-cells compared with XPC +/+ wild-type cells (37)(38)(39). Our results show that the XPC KD cells overcome the early stalled cell cycle and replicate their DNA efficiently, albeit with greater infidelity in the days following overactivation of DNA-PK and the NHEJ pathway ( Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, cells escape replicative arrest utilizing DNA damage tolerance mechanisms that include error-free and error-prone DNA repair systems (36). We and others have shown that UV radiation-induced apoptosis is decreased in XPC -/-cells compared with XPC +/+ wild-type cells (37)(38)(39). Our results show that the XPC KD cells overcome the early stalled cell cycle and replicate their DNA efficiently, albeit with greater infidelity in the days following overactivation of DNA-PK and the NHEJ pathway ( Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, apoptosis levels have been shown to be similar or lower in XPC fibroblasts or keratinocytes compared with wild-type cells following UVC 38 or UVB irradiation. 39 Similarly, Ananthaswamy et al 40 reported that XPC À/À mouse skin was more resistant to apoptosis following chronic UV irradiation than wild-type skin.…”
Section: Xpc Gene Defectmentioning
confidence: 99%
“…The same levels of UV-induced apoptosis in XPC cells and normal cells are consistent with the idea that failure to repair UV damage (especially CPD) in the transcriptionally silent regions of the genome or in the non-transcribed strand of active genes does not induce apoptosis. 38 To explain the reduction of apoptosis in XPC-reconstructed epidermis compared with normal counterparts, one could hypothesize that the XPC protein acts as an initiating factor in the DNA damage-mediated signal transduction process, which results in DNA repair or apoptosis. Microarray studies of cisplatin-treated XPC and normal fibroblasts indicated that cell cycle and cell proliferation-related genes are mainly affected by the XPC gene defect.…”
Section: Xpc Gene Defectmentioning
confidence: 99%
“…The structure-specific endonuclease ERCC5 is an indispensable core protein of the nucleotide excision repair (NER) machinery where it carries out the incision of the damage and stabilizes the protein complex on the locally unwound DNA (de Laat et al, 1999). ERCC5 suppresses UV-induced apoptosis through its endonuclease function (Clément et al, 2006) and also through the extrinsic apoptotic pathway involving caspases, but not p53 (Clément et al, 2007). The expression of this gene, as with other members of NER, could be modulated by oxidative stress (Langie et al, 2007).…”
Section: Figmentioning
confidence: 99%